Molecular and clinical features of KATP‐channel neonatal diabetes mellitus in Japan. Issue 7 (29th September 2016) - Hashimoto, Yukiko; Dateki, Sumito; Hirose, Masakazu; Satomura, Kenichi; Sawada, Hirotake; Mizuno, Haruo; Sugihara, Shigetaka; Maruyama, Koichi; Urakami, Tatsuhiko; Sugawara, Hidenori; Shirai, Kenji; Yorifuji, Tohru
Abstract : Background: There are few reports pertaining to Asian patients with neonatal diabetes mellitus (NDM) caused by activating mutations in the ATP‐sensitive potassium channel genes (KATP ‐NDM). Objectives: To elucidate the characteristics of Japanese patients with KATP ‐NDM. Methods: By the amplification and direct sequencing of all exons and exon‐intron boundaries of the KCNJ11 and ABCC8 genes, 25 patients with KATP ‐NDM were identified from a total of 70 patients with NDM. Clinical data were collected from the medical charts. Results: Sixteen patients had mutations in KCNJ11 and nine in ABCC8 . Eight novel mutations were identified; two in KCNJ11 (V64M, R201G) and six in ABCC8 (R216C, G832C, F1176L, A1263V, I196N, T229N). Interestingly, V64M caused DEND (developmental delay, epilepsy, neonatal diabetes) syndrome in our patient, while mutation of the same residue (V64G) had been reported to cause congenital hyperinsulinism. Mutations in ABCC8 were associated with TNDM (4/9) or isolated PNDM (5/9), whereas those in KCNJ11 were associated with more severe phenotypes, including DEND (3/16), iDEND (intermediate DEND, 4/16), or isolated PNDM (6/16). Switching from insulin to glibenclamide monotherapy was successful in 87.5% of the patients. Neurological improvement was observed in two patients, one with DEND (T293N) and one with iDEND (R50P) syndrome. Three others with iDEND mutations (R201C, G53D, and V59M) remained neurologically normal at 5, 1, and 4 years of age, respectively, with early introduction of sulfonylurea. Conclusion: Overall, clinical presentation of KATP ‐NDM in Japanese patients was similar to those of other populations. Early introduction of sulfonylurea appeared beneficial in ameliorating neurological symptoms.